Kerentanaan dan Strategi Adaptasi Masyarakat Terhadap Bencana Rob di Kawasan Pesisir Kecamatan Sayung Kabupaten Demak - Annisa Sarasadi; Iwan Rudiarto (Teknik PWK (Perencanaan Wilayah Kota), 2021)
Sayung Subdistrict is part of Demak Regency which is located in the northern-coastal region has experienced tidal floods with vulnerable socio-economic in decades. This study aims to determine the level of community vulnerability and the effectiveness of the community adaptation strategy in dealing with the tidal flood. Meanwhile, quantitative and qualitative approaches are used to explore people's adaptations and vulnerability. By used a random sampling technique, people in the Siwulan Village, Bedono Village, Timbulsloko Village and Surodadi Village  was choosen as the research's population. The variables are: community's vulnerability (physical, economic, social and cultural); and adaptation strategies. Questionnaires, observations and documentation has been done for data collecting. The Livelihood Vunerability Index (LVI) is used to measure and analyze the variables by using a score-calculation with 4 criteria including very-effective, effective, less-effective, ineffective. Based on the data, structural adaptations, including  road dredging, embankment construction and raise floor elevation are considered effective to very effective. While raising household furniture was considered effective to very-effective by the people of  Bedono Village, Timbulsloko Village and Surodadi Village, while the Sriwulan Village community considered the structural adaptation to be less effective if it was not accompanied by the elevation of the building floor.